Doremena Tourism Village Towards a Leading Destination in Jayapura Regency: Kampung Wisata Doremena Menuju Destinasi Unggulan di Kabupaten Jayapura - Alvian M. Sroyer; Abraham Abraham; Isak Beno; Agustinus Languwuyo; Yacob Ruru; Jonathan K. Wororomi (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
Sustainable tourism development in Yewena Dormena Village is challenging, a village located in Depapre District, Jayapura Regency, Papua, Indonesia. Despite being blessed with natural beauty and cultural heritage, the village grapples with challenges such as limited accessibility due to poor road conditions and lack of public transportation, inadequate public and tourist facilities, and inadequate promotion of potential tourist attractions. This article introduces a comprehensive framework for sustainable tourism development, specifically tailored to the unique cultural and environmental context of Yewena Dormena Village. The project explores the potential of technology in addressing the accessibility and promotion challenges faced by remote tourist destinations. The method used adopts an interdisciplinary approach, integrating insights from environmental science, cultural studies, and business management to provide a more comprehensive understanding of sustainable tourism development in rural Papua. The results of this project include the renovation of two strategic huts on Sao Beach, ongoing road access improvements by the local government, a 25% increase in tourist visits during the program period, collaboration with local youth groups and provincial conservation agencies for the protection of turtle nesting sites on Sao Beach. Economic growth is targetted will reached 25% in first year and tourist satisfaction reached 80% for public facilities and services. The project has made significant strides in laying the foundation for sustainable rural tourism. Future focus on the challenges and opportunities identified will be crucial to the success and sustainability of tourism in the region.